Predictive role of methylarginines in renal failure - Akyurek, Fikret; Celik, Gulperi; Ozturk, Bahadir (Annals of Medical Research, 2021)
Aim: In this study, we aimed to investigate the role of methylarginines in renal failure and the process leading to failure. Acute Renal Failure (ARF) is defined as sudden onset, damage and loss of renal function. Chronic Kidney Disease (CKD) is generally defined as the presence of decreased renal function loss that persists for more than 3 months. Methylarginines are arginine derivatives which inhibit ischemia and vasoconstriction by inhibiting nitric oxide synthesis, causing ischemia and damage. Methylarginines are metabolized mainly in the kidney. Their metabolism is in the form of direct excretion and enzymatic degradation. Material and Methods: The study was conducted from 2017 through 2018 in 89 patient (serum creatinine levels above 1.5 mg/dL) and 54 healthy control cases. Methylarginines were analyzed in positive mode from Turbo Ion Spray Electrospray (ESI) using ABSCIEX API 3200 High Performance Liquid Chromatography mass spectrometry (LC-MS / MS) instrument using C18 column. Urea and creatinine were analyzed by Beckman Coulter AU5800 Series. Results were evaluated with SPSS system.Results: A significant difference was found in terms methylarginines urea and creatinine when patient and control groups compared. However, only creatinine and creatinine clearance values differences were found in patient groups in terms of acute and chronic renal failure (respectively, p = 0.001 for creatinine and p = 0.028 for creatinine clearance).There was no difference in terms of other parameters.Conclusions: Methylarginines can be considered as new and high potential biomarkers for evaluating renal function. However, it is not considered to be adequate for show the prognosis of the disease